Eksplorasi-Karakterisasi Morfologi Tanaman Kakao Lokal Di Pulau Bangka: Eksplorasi-Karakterisasi Morfologi Tanaman Kakao Lokal Di Pulau Bangka - Maera Zasari; Rostiar Sitorus (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2022)
The diversity of genetic material determines the success of cocoa production. improvement and breeding programs. Enrichment of genetic material for Bangka cocoa can be achieved through exploration and characterization of morphological features or characters of accessions, clones, and/or varieties. To determine the level of diversity of qualitative and quantitative traits. Morphological exploration and characterization was aimed at identifying the diversity of Bangka cocoa as an effort to increase the efficiency of utilization of local genetic material. The research used survey, and direct characterization (purposive sampling). Exploration to obtain a cocoa plant passport consists of accession number, accession name, location of origin, owner's name, age of plant, and land area. Characterization to obtain the identity of qualitative and quantitative characters from leaves, flowers, fruits, and seeds refers to “The Systematic Description of Cacao Clones. The results of the exploration-characterization obtained 29 accessions of cocoa from Bangka, which had very diverse morphological characters. Diversity is evidenced by wide phenotypic variability even though it has narrow genetic variability, and the similarity level of some accessions is quite low, namely <50%.